Dielectron reconstruction in Ag+Ag collisions at sqrt(s_NN) = 2.55 GeV with HADES - Otto, Jan-Hendrik; Justus Liebig University Giessen (My University, 2022)
The study of strongly interacting matter under extreme conditions in terms of temperature and pressure has moved more and more in the focus of high energy physics over the last decades. These conditions can be created in the collision of heavy-ions at various facilities around the world, together covering a broad range of collision energies starting in the GeV region and ranging up to energies of several TeV. In order to study the medium created in such collisions and get an insight in the underlying processes, dileptons are ideal messengers as they do not interact strongly and can therefore leave the medium unharmed carrying their initial properties to the particle detectors. They thus reveal the thermal conditions and the lifetime of the medium but also give insights into meson properties at high densities. One of the experiments dedicated to the investigation of strongly interacting matter is the High Acceptance DiElectron Spectrometer (HADES). It is a versatile detector with particular focus on dielectron measurements in pion, proton, deuteron and (heavy-) ion-induced reactions using proton or nucleus targets in the SIS-18 energy range (1-2 GeV/nucleon). Its excellent particle identification capabilities also allow for the investigation of hadronic observables. The analysis of a high statistics sample of Ag+Ag collisions (4.5 billion events for 0 - 40 % centrality) at sqrt(s_NN) = 2.55 GeV measured by HADES is presented with respect to dielectron production in this work. The recently upgraded HADES RICH detector leads to an unprecedented quality and signal-to-background ratio in the detection of these extremely rare probes. Due to the large number of reconstructed Cherenkov photons it is possible for the first time ever, to efficiently identify and reject electrons produced in conversion processes by a simple count of measured photons. The obtained dielectron spectrum shows a signal up to the phi meson mass region and is compared to simulated hadronic cocktail and nucleon-nucleon reference spectra revealing a strong contribution from the hot and dense phase quantified by the dielectron excess ratio R_AA. The multiplicities of the hadrons are estimated in an analysis of the decay channels pi^0/eta -> 2 gamma -> 4e and omega -> e+e- in the same data set. The slope of the in-medium contribution allows for the extraction of the mean medium temperature. A differential analysis in bins of centrality enables the study of these observables in dependence on the system size. Furthermore, a differential analysis in pair momentum is performed showing a significant change in the line-shape of the spectrum in the rho-omega mass region with increasing (transverse) pair-momentum which suggests a substantial modification of the meson properties in the medium. Previous HADES measurements of Au+Au collisions at sqrt(s_NN) = 2.42 GeV and Ar+KCl at sqrt(s_NN) = 3.18 GeV provide data for comparison and to study energy and system-size dependence of the obtained results.
In the second part of this work the calculation of spectral functions with the Functional Renormalization Group (FRG) including one-loop self-energies in a self consistent way is presented. Spectral functions are defined as the imaginary part of the electromagnetic current-current correlation function and provide direct access to thermal photon and dilepton rates. The calculations are performed for the pion and the sigma meson in the O(4) model at vanishing temperature in the chirally broken phase. Comparing the results with those from previous analytically continued FRG calculations, it is demonstrated, how self-consistency at all momenta fixes the relation between particle masses and decay thresholds.
Keywords: ddc:530